Lemmus sibiricus FJ ... - Spitsyn, Vitaly M.; Bolotov, Ivan N.; Kondakov, Alexander V.; Klass, Anna L.; Mizin, Ivan A.; Tomilova, Alena A.; Zubrii, Natalia A.; Gofarov, Mikhail Y. (Zenodo, 2021)
Siberian Lemming Lemmus sibiricus (Kerr, 1792) Type locality: The northern parts of the Uralian chain of mountains, and on the river Oby [cytb sequence of a topotype: AJ012671] (Kerr 1792; Fedorov et al. 1999). Synonyms: L. obensis Brants, 1827 [TL: Mouth of the Obi River, Siberia, Russia] (Ellerman 1949; Hinton 1926); L. obensis bungei Vinogradov, 1926 [TL: Mostakh Island near the Lena River mouth, Yakutia, Russia; cytb sequence of a topotype: FJ025981] (Abramson et al. 2008; Baranova & Gromov 2003); L. sibiricus West Palearctic sensu Abramson et al., 2008 (Abramson et al. 2008). Distribution: Euro-Siberian Arctic species. Arctic Europe east of the Kola Peninsula and Arctic Siberia up to the Lena Delta (Abramson et al. 2008; Abramson & Petrova 2018). Comments: L. obensis was considered a junior synonym of Kerr’s taxon based on a close proximity of the type localities and morphological data (Ellerman 1949). This solution was confirmed on the basis of molecular genetic research (Abramson et al. 2008). ... : Published as part of Spitsyn, Vitaly M., Bolotov, Ivan N., Kondakov, Alexander V., Klass, Anna L., Mizin, Ivan A., Tomilova, Alena A., Zubrii, Natalia A. & Gofarov, Mikhail Y., 2021, A new Norwegian Lemming subspecies from Novaya Zemlya, Arctic Russia, pp. 93-117 in Ecologica Montenegrina 40 on page 115, DOI: 10.37828/em.2021.40.8, http://zenodo.org/record/13233031 ...